Study on Corticosteroids use Pattern in Dermatological Practice and Investigating Adverse Effect of Corticosteroids Including its Associated Factors - Shakya Shrestha, S.; Bhandari, M.; Shrestha, R.; Thapa, S.R.; Karki, A.; Prajapati, M.; Shrestha, S.; KC, S.; Karna, D. (Kathmandu University Medical Journal, 2017)
Background Corticosteroids are highly effective drugs with anti-inflammatory and immunosuppressive properties. Due to this, they have become a mainstay of pharmacotherapy in dermatology. However, improper and long term uses are associated with a number of serious adverse effects.Objective To investigate the corticosteroids use pattern, adverse effects and various factors associated with adverse effects in dermatological practice.Method A cross-sectional study was conducted in a dermatology department of tertiary care hospital. All patients using at least one corticosteroids, either topically or systemically or the combination were included in this study. Informed consent was taken from the patients and interviewed using structured questionnaire. Statistical analysis was performed by using SPSS 20. p-value < 0.05 was considered as statistically significant.Result Among the 60 participants under this study, 81.67% of them were females. The mean (±SD) age of the patients was 31.03 years (±15.0). A majority (58.30%) of the patients was prescribed with topical corticosteroids with low potency (25%). Most of them had used corticosteroids for urticaria. Adverse effects were reported by 33.30% of the patients. The most common adverse effect reported was the shedding of skin. Adverse effects was significantly associated with gender; use of systemic corticosteroids; regular use of corticosteroids; discontinuation of dose abruptly; and missed dose. However, there was no significant association between adverse effects and the duration of use of corticosteroids.Conclusion In conclusion, the present study suggested that the proper counselling and clear instruction regarding the use of corticosteroid should be provided to the patients for avoiding the abrupt discontinuation of the prescribed medication leading to treatment failure.